The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1098/rspb.2003.2440
|View full text |Cite
|
Sign up to set email alerts
|

Why are dengue virus serotypes so distantly related? Enhancement and limiting serotype similarity between dengue virus strains

Abstract: Dengue virus, the causative agent of dengue fever, has four major serotypes characterized by large genetic and immunological distances. We propose that the unusually large distances between the serotypes can be explained in the light of a process of antibody-dependent enhancement (ADE) leading to increased mortality. Antibody-dependent enhancement results from a new infection with a particular serotype in an individual with acquired immunity to a different serotype. Classical dengue fever causes negligible mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…model assumes that immunity to reinfection with a previously experienced serotype is permanent, consistent with empirical data (3), and in agreement with previous mathematical models of dengue (28)(29)(30)(31)(32). On the basis of findings from epidemiological studies, we also assume that the risk of developing DHF is higher in secondary (or later) infections than in primary infections; we consider this increased risk to be the sole effect of ADE, in contrast to previous models wherein ADE is assumed to enhance either susceptibility to reinfection with a heterologous serotype (28,33,34), an infected individual's transmissibility (30,31,34), or a host's mortality (34,35).…”
Section: Resultsmentioning
confidence: 97%
“…model assumes that immunity to reinfection with a previously experienced serotype is permanent, consistent with empirical data (3), and in agreement with previous mathematical models of dengue (28)(29)(30)(31)(32). On the basis of findings from epidemiological studies, we also assume that the risk of developing DHF is higher in secondary (or later) infections than in primary infections; we consider this increased risk to be the sole effect of ADE, in contrast to previous models wherein ADE is assumed to enhance either susceptibility to reinfection with a heterologous serotype (28,33,34), an infected individual's transmissibility (30,31,34), or a host's mortality (34,35).…”
Section: Resultsmentioning
confidence: 97%
“…The precise immunological consequences of ADE are not fully understood, but there are two alternative assumptions that can be made: (i) ADE can result in increased transmission, by either increased susceptibility to infection after a primary infection (32) or increased infectiousness with a secondary infection (25), perhaps through an increase in viral titers (ref. 33; both variations lead to similar results); or (ii) ADE can result in increased mortality after a secondary infection (27). Here, we focus on assumption i: increased susceptibility to infection after a primary infection, regulated by the parameter .…”
Section: Methodsmentioning
confidence: 92%
“…Previous theoretical work has demonstrated that if ADE is assumed to increase transmission, then coexistence and cyclic, possibly chaotic, strain fluctuations are promoted (25,26). However, if ADE is instead assumed to increase mortality and shorten the effective infectious period, it may decrease persistence (27).…”
Section: Alternative Hypothesesmentioning
confidence: 99%
“…We believe this assumption is a reasonable because of the low case fatality rate of DHF (Ϸ0.01) and the much lower fatality rate of dengue infection (Ϸ0.0001) in Thailand (34). The work of Kawaguchi and Rohani (30,35) suggests that the dynamics of dengue are significantly impacted by dengue-induced mortality only at much higher levels of mortality than are observed. The rate of recovery, given by , is assumed to be equal for primary and secondary infections.…”
Section: Methodsmentioning
confidence: 94%
“…Research groups have explored the effects of ADE on the dynamics of dengue transmission by using several different approaches (25,27,29,30). Feng (29) examined the effect of ADE in a two-serotype model via the inclusion of a parameter that increased the susceptibility of those individuals who had previously been exposed to one serotype.…”
mentioning
confidence: 99%